The fentanyl-specific antibody FenAb024 can shield against carfentanil effects - Urban, Katharina; Gkeka, Anastasia; Chandra, Monica; Greiner, Dennis; Pollich, Selina; Ruf, Sandra; Kelemen, Yosip; Sundermann, Tom R.; Pravetoni, Marco; Baehr, Carly; Stebbins, Erec; Papavasiliou, Nina; et al. (Toxicology letters)
The surge in opioid-related deaths, driven predominantly by fentanyl and its synthetic derivatives, has become a critical public health concern, which is particularly evident in the United States. While the situation is less severe in Europe, the European Monitoring Centre for Drugs and Drug Addiction reports a rise in drug overdose deaths, with emerging concerns about the impact of fentanyl-related molecules. Synthetic opioids, initially designed for medical use, have infiltrated illicit markets due to their low production costs and high potency, with carfentanil posing additional threats, including potential chemical weaponization. Existing overdose mitigation heavily relies on naloxone, requiring timely intervention and caregiver presence, while therapeutic prevention strategies face many access challenges. To provide an additional treatment option, we propose the use of a fentanyl-specific monoclonal antibody (mAb), as a non-opioid method of prophylaxis against fentanyl and carfentanil. This mAb shows protection from opioid effects in a pre-clinical murine model. mAbs could emerge as a versatile countermeasure in civilian and biodefense settings, offering a novel approach to combat opioid-associated mortality.
Online verfügbar 6 April 2024, Version des Artikels 13 April 2024
Gesehen am 15.11.2024